ALGORITHM OF AIR TRAFFIC PRE-TACTICAL PLANNING SYSTEM - V. V. Vorobyev; A. S. Kharlamov (Научный вестник МГТУ ГА)
The organization of air traffic management planning in Russian Federation is examined in this article. The capacity of the sectors is one of the main parameters, used with air traffic management planning. The algorithm of pre- tactical air traffic management planning is designed to avoid excess of the capacity of the air traffic on the pre- tactical phase. This algorithm was tested using the simulator tower type “Sintez-TC-V”. The result of it is increase of the efficiency of air traffic management planning.